Less Common Nontraumatic Bowel Perforations: Diagnosis and Management through a Retrospective Study. Issue 4 (April 2013) - Gourgiotis, Stavros; Liakos, Nikolaos; Gemenetzis, George; Seretis, Charalampos; Aloizos, Stavros; Vougas, Vasilis; Drakopoulos, Spyros
Nontraumatic bowel perforation has always been a consideration because of associated morbidity and mortality. The aim of this study is to define etiologies, treatment, and outcomes as well as to highlight difficulties in the diagnosis and management of nontraumatic bowel perforation. We conducted a retrospective study of 35 patients with less common nontraumatic bowel perforations hospitalized during a six-year period. The most common cause was ulcerative colitis (34.3%). Abdominal pain was the constant symptom. Physical examination showed signs of peritoneal irritation in 29 cases. The abdominal radiograph failed to reveal abnormal findings in two patients; the abdominal computed tomography scan confirmed the diagnosis in all cases. Twenty patients (57.1%) were operated on within 24 hours of developing perforation, whereas seven patients (20%) were initially misdiagnosed. Most of the perforations were located only in the large intestine (60%). There was only one perforation in 25 patients (71.5%) and two or more perforations in 10 patients (28.5%). Many less common diseases are responsible for the spontaneous perforation of the bowel. Early diagnosis before the patient's general condition deteriorates decreases mortality and morbidity rates. Adequate resuscitation and emergency laparotomy followed by resection with or without anastomosis remains the treatment of choice.